The replicability of ICD-11 complex post-traumatic stress disorder symptom networks in adults. (9th January 2019) - Knefel, Matthias; Karatzias, Thanos; Ben-Ezra, Menachem; Cloitre, Marylene; Lueger-Schuster, Brigitte; Maercker, Andreas
Abstract : Background: The ICD-11 includes a new disorder, complex post-traumatic stress disorder (CPTSD). A network approach to CPTSD will enable investigation of the structure of the disorder at the symptom level, which may inform the development of treatments that target specific symptoms to accelerate clinical outcomes. Aims: We aimed to test whether similar networks of ICD-11 CPTSD replicate across culturally different samples and to investigate possible differences, using a network analysis. Method: We investigated the network models of four nationally representative, community-based cross-sectional samples drawn from Germany, Israel, the UK, and the USA (total N = 6417). CPTSD symptoms were assessed with the International Trauma Questionnaire in all samples. Only those participants who reported significant functional impairment by CPTSD symptoms were included ( N = 1591 included in analysis; mean age 43.55 years, s.d. 15.10, range 14–99, 67.7% women). Regularised partial correlation networks were estimated for each sample and the resulting networks were compared. Results: Despite differences in traumatic experiences, symptom severity and symptom profiles, the networks were very similar across the four countries. The symptoms within dimensions were strongly associated with each other in all networks, except for the two symptom indicators assessing aspects of affective dysregulation. The most central symptoms were 'feelings of worthlessness' and 'exaggerated startle response'. Conclusions: The structure of CPTSD symptoms appears very similar across countries. Addressing symptoms with the strongest associations in the network, such as negative self-worth and startle reactivity, will likely result in rapid treatment response. Declaration of interest: A.M. and M.C. were members of the World Health Organization (WHO) ICD-11 Working Group on the Classification of Disorders Specifically Associated with Stress, reporting to the WHO International Advisory Group for the Revision of ICD-10 Mental and Behavioural Disorders. The views expressed in this article are those of the authors and do not represent the official policies or positions of the International Advisory Group or the WHO.